Production of scandium radionuclides for theranostic applications: towards standardization of quality requirements - R. Mikolajczak; S. Huclier-Markai; C. Alliot; F. Haddad; D. Szikra; V. Forgacs; P. Garnuszek (SpringerOpen, 2021)
Abstract In the frame of "precision medicine", the scandium radionuclides have recently received considerable interest, providing personalised adjustment of radiation characteristics to optimize the efficiency of medical care or therapeutic benefit for particular groups of patients. Radionuclides of scandium, namely scandium-43 and scandium-44 (43/44Sc) as positron emitters and scandium-47 (47Sc), beta-radiation emitter, seem to fit ideally into the concept of theranostic pair. This paper aims to review the work on scandium isotopes production, coordination chemistry, radiolabeling, preclinical studies and the very first clinical studies. Finally, standardized procedures for scandium-based radiopharmaceuticals have been proposed as a basis to pave the way for elaboration of the Ph.Eur. monographs for perspective scandium radionuclides.